The Incidence of Hepatocellular Carcinoma after Balloon-Occluded Retrograde Transvenous Obliteration. (19th March 2015) - Yokoyama, Keiji; Irie, Makoto; Anan, Akira; Yokoyama, Masanori; Tsuchiya, Naoaki; Fukunaga, Atsushi; Takata, Kazuhide; Tanaka, Takashi; Hirano, Genryu; Morihara, Daisuke; Takeyama, Yasuaki; Shakado, Satoshi; et al.
Abstract : Balloon-occluded retrograde transvenous obliteration (BRTO) is a highly effective therapy for gastric varices with liver cirrhosis. We have investigated the incidence of hepatocellular carcinoma (HCC) after BRTO. We enrolled 71 patients with viral hepatitis in which HCC had not appeared with liver imaging findings at the time of BRTO. The overall survival rate after BRTO was 86.8%, 76.1%, and 50.5% at 1, 3, and 5 years. The occurrence rate of HCC after BRTO was 20.9%, 41.1%, and 60.7% at 1, 3, and 5 years, especially showing a higher occurrence of HCC at one year. Meanwhile, the occurrence rate of HCC after treatment which excluded BRTO for esophagogastric varices in patients was 6.3%, 19.2%, and 42.5% at 1, 3, and 5 years. The log-rank test revealed that the occurrence rate of HCC after treatment was significantly higher in the BRTO group compared with that in the non-BRTO group (P = 0.0447 ). The recurrence rate of HCC after BRTO was 35.8% and 80.0% at 1 and 3 years. The present study demonstrated a high incidence of HCC after BRTO in liver cirrhosis patients with viral hepatitis infection. We have suggested the potential for BRTO to accelerate hepatocarcinogenesis.